The Regulating Network and Significance of Neutrophils in Aortic Valve Stenosis - Du, Hanghang; Cai, Peian; Jiao, Xuan; Liu, Chang; Tian, Hai; Chen, Wei (Journal of Contemporary Medical Sciences, 2025)
Objective: Valves replacement is the only strategy for aortic valve stenosis (AVS) treatment. A comprehensively understanding about pathogenesis of AVS would be helpful for individualized treatment of AVS in the future. Methods: The mRNA profiles of Normal and AVS samples were harvested from the Gene Expression Omnibus database. The differently expressed genes (DEGs) were identified via limma package. Among the DEGs, the least absolute shrinkage and selection operator (LASSO) logistic regression and random forest (RF) analysis were utilized to identify the biomarkers for AVS. Cibersort package were used to assess the difference of infiltration levels of 22 types of immune cells between Normal and AVS groups. Besides, the most significant immune cell was also evaluated by RF analysis. The relationships between the identified biomarkers and immune cells were assessed via correlation analysis. Set Enrichment Analysis (GSEA) of single genes was conducted to reveal the potential mechanisms involved by the biomarkers. And the DGIdb database was utilized for the drug prediction for the crucial biomarkers. Results: There was a total of 543 DEGs including 315 up-regulated and 228 down-regulated DEGs. Among them, CXCL5, COL4A3 and EPB41L4B were the significant biomarkers of AVS. The T cells CD4 memory resting and activated, plasma cells, M0 macrophages, T cells regulatory (Tregs) and neutrophils were the significantly infiltrative immune cells in which neutrophils was the most important immune cell type in AVS. CXCL5 could regulate all significantly infiltrative immune cells involved in AVS development, while COL4A3 and EPB41L4B only mediated the neutrophils in AVS. Moreover, ECM receptor interaction, focal adhesion, chemokine signaling pathways and insulin signaling pathway were the main mechanisms involved by the biomarkers. Collagenase clostridium histolyticum and Ocriplasmin was the potential drug for COL4A3. Conclusion: The infiltration of neutrophils mediated by CXCL5, COL4A3, and EPB41L4B may be a pivotal mechanism of AVS.